Assessing the key game-related statistics in Brazilian professional basketball according to season phase and final score difference - Giovanini, B.; Conte, D.; Ferreira-Junior, A.; Nascimento, V. B. (International Journal of Performance Analysis in Sport, 2021)
This study aimed to identify the game-related statistics that best discriminate winning and losing teams during the regular season and playoff phase of Brazilian professional basketball. Data were retrieved from game-related statistics of 1271 games (1048 from regular season and 223 from playoffs phase) of five seasons between 2014 and 2019 of the Brazilian professional basketball league [Novo Basquete Brasil (NBB)]. All games were clustered into close, balanced, and unbalanced games. A discriminant analysis was performed. Results showed that defensive rebounds (SC = 0.407) were determinant to win close games in the regular season, while defensive rebounds, assists, and 3-point shooting efficiency were determinant (SC > 0.3) to win balanced and unbalanced games in this phase. In the playoff phase, winning teams performed more defensive rebounds and assists (SC > 0.3), having relevant contribution of 3-point shooting efficiency (SC = 0.311) in close games, and 2-point shooting efficiency (SC = 0.336) in balanced games. These findings should be useful for coaches to plan training and playing strategies emphasising the game-related statistics that are more determinant to the game outcome.